Opsin genes of select treeshrews resolve ancestral character states within Scandentia. Issue 4 (24th April 2019) - Duytschaever, Gwen; Janiak, Mareike C.; Ong, Perry S.; Wells, Konstans; Dominy, Nathaniel J.; Melin, Amanda D.
Abstract : Treeshrews are small, squirrel-like mammals in the order Scandentia, which is nested together with Primates and Dermoptera in the superordinal group Euarchonta. They are often described as living fossils, and researchers have long turned to treeshrews as a model or ecological analogue for ancestral primates. A comparative study of colour vision-encoding genes within Scandentia found a derived amino acid substitution in the long-wavelength sensitive opsin gene ( OPN1LW ) of the Bornean smooth-tailed treeshrew ( Dendrogale melanura ). The opsin, by inference, is red-shifted by ca 6 nm with an inferred peak sensitivity of 561 nm. It is tempting to view this trait as a novel visual adaptation; however, the genetic and functional diversity of visual pigments in treeshrews is unresolved outside of Borneo. Here, we report gene sequences from the northern smooth-tailed treeshrew ( Dendrogale murina ) and the Mindanao treeshrew ( Tupaia everetti, the senior synonym of Urogale everetti ). We found that the opsin genes are under purifying selection and that D. murina shares the same substitution as its congener, a result that distinguishes Dendrogale from other treeshrews, including T. everetti. We discuss the implications of opsin functional variation in light of limited knowledge about the visual ecology of smooth-tailed treeshrews.